2011
DOI: 10.1186/1471-2105-12-480
|View full text |Cite
|
Sign up to set email alerts
|

GC-Content Normalization for RNA-Seq Data

Abstract: BackgroundTranscriptome sequencing (RNA-Seq) has become the assay of choice for high-throughput studies of gene expression. However, as is the case with microarrays, major technology-related artifacts and biases affect the resulting expression measures. Normalization is therefore essential to ensure accurate inference of expression levels and subsequent analyses thereof.ResultsWe focus on biases related to GC-content and demonstrate the existence of strong sample-specific GC-content effects on RNA-Seq read cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
650
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 777 publications
(666 citation statements)
references
References 38 publications
14
650
0
2
Order By: Relevance
“…Counts were generated from alignment files in BAM format using a custom Python To correct for possible GC or length bias, data were normalized using the EDASeq R 467 package (Risso, 2011). Differential expression analysis and gene ontology (GO) 468 term and pathway enrichment analyses were conducted using the EdgeR package 469 (Robinson et al, 2010).…”
mentioning
confidence: 99%
“…Counts were generated from alignment files in BAM format using a custom Python To correct for possible GC or length bias, data were normalized using the EDASeq R 467 package (Risso, 2011). Differential expression analysis and gene ontology (GO) 468 term and pathway enrichment analyses were conducted using the EdgeR package 469 (Robinson et al, 2010).…”
mentioning
confidence: 99%
“…It has been shown that these abundance measures are prone to biases correlated with the nucleotide composition [14,17] and length of the transcript [1,18]. Several within and between sample correction and normalisation procedures have recently been developed to address these biases either as nucleotide composition effects [17] or various combinations of nucleotide, length or library preparation biases [14,15].…”
mentioning
confidence: 99%
“…Various tools are able to correct for this type of bias, like EDASeq (Risso et al 2011) and cqn (Hansen et al 2012) where the GC bias or length bias are included as covariates.…”
Section: Normalizationmentioning
confidence: 99%
“…It is lane-dependent and probably introduced during the library preparation step (Risso et al 2011).…”
Section: Normalizationmentioning
confidence: 99%